Effect of alumina trihydrate as additive on the mechanical properties of kenaf/polyester composite for plastic encapsulated electronic packaging application - A. Atiqah; M.N.M Ansari; M.S.S. Kamal; A. Jalar; N.N. Afeefah; N. Ismail (Journal of Materials Research and Technology, 2020)
This paper mainly focuses on the suitability of using kenaf/polyester composites for potential plastic encapsulated electronic packaging. The usage of natural fiber, such as kenaf fiber which has been recognized as for green fiber is the potential substitute in plastic encapsulation composites. The use of microsized Alumina Trihydrate (ATH) as the additive in the formulations is to reduce the hygroscopic tendency of the composites. In this research, there are six compositions of the plastic encapsulation composites fabricated using hand lay-up followed by the vacuum infusion method. Moreover, the amount of additive of microsized ATH was varied (2.5, 5 and 7.5 wt%) in kenaf/polyester composites is also to observe the performance of mechanical properties such as tensile, flexural and impact strength. Then, evidence that the effect of microsized ATH additive had occurred between kenaf/polyester was identified by using Scanning Electron Microscope (SEM). The results revealed that the addition of microsized ATH at 5 wt% of kenaf/polyester composites improved slightly higher than unfilled ATH for the tensile and flexural strength by 1.7% and 2.13%. Also, the impact strength can reach up to 28% for 5 wt% ATH filled and the reduced water uptake was observed when increasing of microsized ATH content from 2.5 to 7.5 wt%. Thus, this suitability of microsized ATH as an additive could be a potential material used for plastic encapsulation for electronic packaging applications.